REDUCING STUDENTS’ FOREIGN LANGUAGE ANXIETY IN SPEAKING CLASS THROUGH COOPERATIVE LEARNING - Susidamaiyanti Susidamaiyanti (Asosiasi Dosen Perguruan Tinggi Islam, 2018)
One of the challenges in teaching English as a foreign language to students in Indonesia is the existence of Foreign Language Anxiety (FLA) that are faced by students at any level of education. FLA has hindered the students in mastering English, especially in Speaking Skill, it is shown by their performances in the class which are too nervous, shy, unwilling to participate and lack of confidence.Gardner and McIntyre,(1987) stated that FLA negatively impacts the quality of learning and is a critical factor in learners’ success or failure in learning a foreign language. Based on the aforementioned statements, it means reducing students’ language anxiety can enhance their overall learning experience and improve motivation and achievement.Thus, for many years, some researchers have attempted to find the most suitable techniques and methods to help students overcome this problem. Some of which is by providing them a conducive learning environment, the culture of caring and of course, a non-threatening atmosphere in the classroom. For that reason, this paper isintended to propose a technique to reduce the students’ anxiety; that is cooperative learning. By using cooperative learning, it is expected that it can overcome this problem, as this technique offers a good language-learning environment in which the process of learning dealing with cooperativeness rather than competitiveness. This is in line with Krashen (1982). He, through his Affective Filter Hypothesis, contends that one of the factors of language acquisition to happen is in a low-filter language-learning environment.